Influence of Physical Fitness Level on Student Self-Motivation in Public Secondary Schools in Rulindo District, Rwanda - Theogene, Ndacyayisenga; Hesbon, Andala O. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study assessed how physical fitness levels influence student self-motivation in public secondary schools in Rulindo District, Rwanda. Using a descriptive research design, data were collected from 301 teachers and 98 head teachers through questionnaires and semi-structured interviews respectively. Findings revealed that 39.7% of teachers acknowledged students use sports to make effective school progress, though 58.9% indicated students never use sports tools regularly. Correlation analysis showed a strong positive relationship (r = 0.684, p < 0.05) between physical fitness level and student self-motivation, with regression analysis indicating that physical fitness explains 77.2% of variance in student self-motivation. The study concludes that enhanced physical fitness levels significantly improve student self-motivation, though challenges including inadequate sports infrastructure, insufficient professional training for teachers, and limited frequency of sports activities constrain effectiveness. Recommendations include investing in sports facilities, providing professional development for teachers in physical education pedagogy, and establishing regular physical activity schedules to maximize motivational benefits.